Bi-Cortical transhumeral drilling for biceps tenodesis - Is it safe? - Bancha Chernchujit; Amolnat Chiarnpattanodom; Sumit Agrawal (Elsevier, 2023)
Background: Biceps tenodesis is an effective procedure performed to treat shoulder pain originating from the long head biceps tendon. In arthroscopic biceps tenodesis unicortical drilling of the humerus is more commonly practiced as it is considered safe to the vital structures lying posterior to the proximal humerus. Many surgeons are wary of the bi-cortical approach as it poses a risk to these vital structures. The aim of this study was to establish whether bi-cortical drilling in proximal humerus is safe or not. Our second purpose was to find a safe zone (if any) for bi-cortical drilling if bi-cortical drilling is safe. Methods: This study is a descriptive study conducted on cadaveric shoulders. Bilateral shoulders and arms of ten fresh-frozen cadavers (mean age 77.7 y) were dissected. Four landmarks in the dissected humerus were identified. They were superior margin of the bicipital groove, center of the bicipital groove, upper and lower border of pectoralis major insertion. Bi-cortical trans-humeral pinning was done in the humerus at all these points so that the pin exited through the posterior cortex of the humerus. The shortest distance between the pin and the nearest vital structure namely axillary nerve, radial nerve, articular surface of the humeral head, and cephalic vein was calculated from each fixed landmark. Results: We established that bi-cortical drilling in proximal humerus was safe. The safe zone established for bi-cortical biceps tenodesis is at the middle of bicipital groove, which is 18.00 ± 4.02 mm inferior to the groove's upper border. The boundaries of the safe zone lie 9.39 mm superiorly and 9.40 mm inferiorly to the middle of the bicipital groove. Conclusion: The center of the established safe zone for bi-cortical trans-humeral pinning was 18 mm inferior to the bicipital groove's upper border.